Complementation of a mutation in CpSRP43 causing partial truncation of light-harvesting chlorophyll antenna in Chlorella vulgaris. Issue 1 (December 2017) - Shin, Won-Sub; Lee, Bongsoo; Kang, Nam; Kim, Young-Uk; Jeong, Won-Joong; Kwon, Jong-Hee; Jeong, Byeong-ryool; Chang, Yong
Abstract Photosynthesis of microalgae enables conversion of light energy into chemical energy to produce biomass and biomaterials. However, the efficiency of this process must be enhanced, and truncation of light-harvesting complex (LHC) has been suggested to improve photosynthetic efficiency. We reported an EMS-induced mutant (E5) showing partially reduced LHC inChlorella vulgaris . We determined the mutation by sequencing the whole genome of WT and E5. Augustus gene prediction was used for determining CDS, and non-synonymous changes in E5 were screened. Among these, we found a point mutation (T to A) in a gene homologous to chloroplast signal recognition particle 43 kDa (CpSRP43). The point mutation changed the 102nd valine to glutamic acid (V102E) located in the first chromodomain. Phylogenetic analyses of CpSRP43 revealed that this amino acid was valine or isoleucine in microalgae and plants, suggesting important functions. Transformation of E5 with WT CpSRP43 showed varying degrees of complementation, which was demonstrated by partial recovery of the LHCII proteins to the WT level, and partially restored photosynthetic pigments, photosynthetic ETR, NPQ, and growth, indicating that the V102E mutation was responsible for the reduced LHC in E5.